Mass Balance and Metabolic Profiling of Avacopan, a Selective C5a Receptor 1 Antagonist, in Healthy Humans - Song, Yang; Miao, Shichang; Zhao, Ruiping; Liu, Xiaoli; Tai, Ezra; Krasinski, Antoni; Zeng, Yibin; Zhang, Penglie; Wills, Sarah; Pennell, Andrew; Bekker, Pirow; Oberoi, Rajneet K. (Current Drug Metabolism, 2025)
Introduction: Avacopan (Tavneos®) is approved as an oral adjunctive treatment at a dose of 30 mg twice daily with food for adult patients with severe active granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) in combination with standard therapy including glucocorticoids.MethodsIn this pharmacokinetic (PK) study, the absorption, metabolism, and excretion of avacopan were evaluated following a single 100 mg/400 μCi oral 14C-avacopan dose solution in six healthy male participants. The mass balance recovery, plasma concentrations, and metabolite profile in plasma, urine, and feces were determined.ResultsFecal and renal excretion accounted for 77.2% and 9.5%, respectively, of the total administered radioactivity, with none of the mono- or bis-oxidation metabolites present at greater than 7% of the total radioactive dose. In urine, intact avacopan was present at <1% of the radioactive dose. In feces, intact avacopan was present at 8.7%, which represented 6.7% of the total radioactive dose, suggesting at least 93.3% of the radioactive dose was absorbed. The predominant component in plasma was avacopan, which accounted for 18.0% of the dose. The major circulating metabolite, M1, a monohydroxylation metabolite with similar potency in C5a receptor inhibition as avacopan, accounted for 11.9% of the total radioactivity.DiscussionThe primary route of elimination of avacopan is phase I metabolism, followed by biliary excretion of the metabolites. CYP3A4 is the primary isozyme involved in the in vitro metabolism of avacopan and formation of metabolite M1.ConclusionStudy results provide a definitive assessment of the absorption, elimination, and nature of metabolism of avacopan in humans.
Keywords: MPA